Narrative Nuances: Analyzing Speech Acts in Soman Chainani's 'The School for Good and Evil' Movie - Fitria Aprilia; Neisya Neisya; Whariyanti Whariyanti (Universitas Hamzanwadi, 2023)
This research analyzes the different types of speech acts in the movie